Evaluation of hibiscus esculentus (okra) gum as a natural binder in sustained release tablets of propranolol hydrochloride / Nurul Dhania Zaharuddin - Nurul Dhania, Zaharuddin (2015)
The application of natural polysaccharides obtained from plant mucilages as an excipient has proven to be effective in pharmaceutical dosage forms having various characteristics that contribute to different functions in the drug delivery system. In this study, okra gum which was extracted from the pods of Hibiscus esculentus was evaluated on its application as a natural binder in the development of sustained release tablets of propranolol hydrochloride, an antihypertensive drug. Unripe Hibiscus esculentus fruits were obtained freshly from the local market, sliced and soaked immediately in distilled water and filtered to extract out the mucilage, precipitated using acetone as a drying agent, further dried in a desiccator and grounded and sieved to produce okra powder. Its physical characterization such as solubility, pH, moisture content and viscosity were studied. Its nature and morphology were observed using XRay Diffraction Analysis (XRD) and Field Emission Scanning Electron Microscope (FESEM). Its thermal characteristics were determined using Differential Scanning Calorimetry (DSC) and its infrared spectrum had been developed using Fourier Transform Infra-red (FTIR). Okra powder was then used as a binder and retarding polymer and sodium bicarbonate was used as an effervescent agent to produce floating sustained release tablets of propranolol hydrochloride. Seven formulations (F1-F7) were finalized and the best formulation (F5) of floating sustained release tablet that made up consistent and smoothest release pattern throughout the 24 hours was identified. These floating sustained release tablets were developed to create a uniform drug therapy that is specifically released in the upper part of gastrointestinal tract. Its floating behavior shows that tablet was able to float successfully throughout the whole 24 hours and more. In vitro dissolution profile studies indicated that okra gum was able to control drug release by retarding its release in a moderate and consistent manner up iv to 24 hours. Tablet was also compared to the commercial conventional propranolol immediate release tablet and it was found that propranolol sustained release tablet could release drug at a moderate rate throughout the prolonged duration as compared to the conventional propranolol tablet that was completely released within the first 15 minutes. The swelling index study shows that higher amount of okra in tablets causes higher swelling index. Its tensile strength was evaluated by conducting hardness and friability tests. Results indicate that tablets with higher okra concentration increases the hardness of tablets and decrease its friability. This explains that okra is able to improve the durability and strength of tablets. Hence, okra gum was affirmed as an effective binder to produce favourable propranolol hydrochloride sustained release tablets.